Green Purchase Intention: Peran Attitude Toward Green Product, Green Customer Value, Dan Green Psychological Benefit - Sri Wulandari; Muhammad Ali Fikri (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2025)
The intention to purchase green products arises from perceptions of value and positive attitudes toward sustainable products, supported by psychological benefits after purchase. This study aims to analyze the influence of attitudes toward green products and green customer value on green purchase intention, with the mediating role of green psychological benefits. The research objects were Aqua consumers in Yogyakarta. The sample was taken using purposive sampling technique with a total of 169 respondents. Data collection methods used questionnaire distribution and analysis using Smart PLS 4.0. The results of the scale test used for validity testing, reliability testing, and hypothesis testing. Hypothesis testing showed that attitude toward green product did not have a positive effect on green purchase intention, but had a positive effect on green psychological benefits. Green psychological benefits have a positive effect on green purchase intentions. Green psychological benefits mediated the positive effect of attitude toward green product on green purchase intention. Furthermore, green customer value did not have a positive effect on green purchase intention, but had a positive effect on green psychological benefits. Green psychological benefits mediated the positive effect of green customer value on green purchase intention. This study provides a novel contribution by demonstrating that green psychological benefit functions as a full mediator between attitude toward green product and green customer value in shaping green purchase intention, a model that has rarely been applied to bottled drinking water consumers in Indonesia, particularly in Yogyakarta.